Pemahaman Terhadap Wanprestasi Debitur: Implikasi Terhadap Manajemen Risiko Kredit di Sektor Perbankan - Rahmawati, Syifa Fitri; Subrata, Rusli (Lembaga Pengembangan Kinerja Dosen, 2024)
Debtor default has significant implications for credit risk management in the banking sector. Default, as the failure of a debtor to fulfill its obligations in repaying a loan, not only has the potential to be detrimental to financial institutions, but can also affect the stability of the financial system as a whole. Therefore, research on this phenomenon is very important. This article aims to provide comprehensive insight into understanding debtor default and its impact on credit risk management in the banking sector. A holistic approach to this understanding includes identifying factors that contribute to default, analyzing the characteristics of vulnerable debtors, and evaluating effective risk mitigation strategies. One important aspect discussed is the factors that cause default, including macroeconomic conditions, changes in an individual's financial situation, and behavioral factors. By understanding the root causes of default, banks can identify potential credit risks early and take appropriate steps to manage them. In addition, this article discusses the importance of debtor profile analysis in identifying characteristics that are vulnerable to default. By leveraging advanced technology and data analysis, banks can strengthen their decision-making processes and improve their ability to manage credit risk. Thus, this article not only provides an in-depth review of understanding debtor default, but also provides insight into how banks can improve their credit risk management through targeted and innovative approaches. In conclusion, a better understanding of the debtor default phenomenon will help banks manage credit risk more effectively and strengthen the resilience of the financial system as a whole.